Domestic hot water design and flow measurements. (October 2021) - Averfalk, Helge; Möllerström, Erik; Ottermo, Fredric
Abstract: In this study, the sizing of primary side components for preparation of domestic hot water are analysed, both qualitatively and based on measurements of domestic hot water demand in one multi-family building with 268 apartments. The collected data spans a period of 18 days during the end of 2020 and is collected in 15-min, 1-min, and 6-s intervals. An overview of the historic development for the design of domestic hot water flow in Sweden is also presented. There is a long-standing argument in Sweden, that the current district heating guidelines result in an overdesign of the flow for domestic hot water. The consequence of this is oversizing heat exchangers and valves in the substations. This study assesses, qualitatively, the issues related to overdesigned primary side valves for preparation of domestic hot water. A revised design for domestic hot water flow for the Swedish context is also conceptualised. The study suggests that an improved design flow for domestic hot water in multi-family buildings can be derived based on empirical measurements. The 15-min intervals are observed to tone down information of peaks to a degree where it is unsuitable to use as basis for a new design flow. The 1-min data does appear to preserve information to a degree where it can be used to assess a design flow when related to data with a 6-s interval. The 6-s data is expected to constitute a resolution that may be less available, and in this study, it constitutes a representation of the real domestic hot water demands. However, to find a fitted curve to empirical data, for the design flow based on number of apartments per multi-family building, the population of datasets needs to be increased.